Mongol History rewritten and relived - Beatrice Forbes Manz (Revue des Mondes Musulmans et de la Méditerranée)
History was an important source for legitimization and for establishing precedents in the medieval Middle East, both for rulers and their subjects. In Iran and Central Asia, the most recent and formative history was that of Mongol conquest and rule ; this was true for Iranians as well as for the Turco-Mongolian ruling class. We see in both regional and dynastic histories the constant elaboration of central issues, particularly the question of the division of the Mongol Empire, and the drama of Islamization. In this paper the author examines the use of history by several rulers who sought to increase their prestige and legitimate their rule through the active imitation of past rulers and the manipulation of historical memories. In their public actions Temür and his Jöchid rival Tokhtamish referred back to both the career of Chinggis Khan and the earlier rivalries between the Ilkhans and the Golden Horde. Shāhrukh, using Islamization as part of his legitimization, imitated the Islamizing Ilkhan, Ghazan. To understand the career of these leaders, we should understand both the historical precedents their actions referred to, and the way in which Mongol history was viewed within their milieu.